1964
DOI: 10.1083/jcb.22.1.127
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the Fine Structure of Lutein Cells

Abstract: Corpus luteum formation was induced in 26-day-old rats which were subsequently hypophysectomized and injected with mammotrophic hormone (MH, LTH). Sections of corpora lutea from these animals were examined with the electron microscope and compared with similarly prepared (Caulfield's fixed, Araldite embedded) corpora from normal pregnancy and from controls, the latter consisting of corpora prior to hypophysectomy and corpora from uninjected rats 7 to 14 days after hypophysectomy. Lutein cells from corpora lute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0

Year Published

1967
1967
1991
1991

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(17 citation statements)
references
References 20 publications
4
13
0
Order By: Relevance
“…This is at variance with the observations of Bjersing et al (1970) who found "no, or almost no, lipid droplets" in the CL of sheep on Days 10 to 13 of the cycle. The obvious accumulation of lipids in the CL of ewes treated with PGF2(t is an involutionary change and is consistent with the ac¬ cepted view that, during the decline in the secretory activity of a steroid secretory cell, the ability to synthesize lipids is retained but the capacity to convert these lipids to steroid hormones is lost (Deane, 1958;Enders & Lyons, 1964).…”
Section: Discussionsupporting
confidence: 70%
“…This is at variance with the observations of Bjersing et al (1970) who found "no, or almost no, lipid droplets" in the CL of sheep on Days 10 to 13 of the cycle. The obvious accumulation of lipids in the CL of ewes treated with PGF2(t is an involutionary change and is consistent with the ac¬ cepted view that, during the decline in the secretory activity of a steroid secretory cell, the ability to synthesize lipids is retained but the capacity to convert these lipids to steroid hormones is lost (Deane, 1958;Enders & Lyons, 1964).…”
Section: Discussionsupporting
confidence: 70%
“…As described in previous studies (Enders and Lyons, 1964;Enders, 1973;Dharmarajan et al, 1983Dharmarajan et al, , 1985, the CL in this study also had a n extensive interstitial space. The precise role of this space is not known, but it is possible that the fluid within it is substantially mobile and may eventually drain into adjacent blood vessels or, alternatively, into the lymphatic drainage of the ovary.…”
Section: Discussionmentioning
confidence: 71%
“…The smooth-surfaced endoplasmic reticulum is characteristically a well developed cytomembrane system in known steroid-producing cells. Thus, a tubular form of smooth-surfaced endoplasmic reticulum is encountered in the corpus luteum (5,25,26,93), in the interstitial cells of the testis (17,18), and in the adrenal cortex (51,54,73). In addition, steroid-producing cells are characterized by the presence in the cytoplasm of mitochondria, Golgi complexes, lipid, and lysosomes (see 54).…”
Section: Discussionmentioning
confidence: 99%